An Improved Murine Pre-Malignant Squamous Cell Model: Tobacco smoke exposure augments NTCU-induced murine airway dysplasia - Dwyer-Nield, Lori D. (Cancer Prev Res (Phila), 2020)
Tobacco smoke-induced squamous cell lung cancer develops from endobronchial dysplastic lesions that progress to invasive disease. A reproducible murine model recapitulating histologic progression observed in current and former smokers will advance testing of new preventive and therapeutic strategies. Previous studies show that prolonged topical application of N-nitroso-tris-chloroethylurea (NTCU) generates a range of airway lesions in sensitive mice similar to those induced by chronic tobacco smoke exposure in humans. To improve the current NTCU model and better align it with human disease, NTCU was applied to mice twice weekly for 4–5 weeks followed by a recovery period before cigarette smoke (CS) or ambient air (control) exposure for an additional 3–6 weeks. Despite the short time course, the addition of CS led to significantly more premalignant lesions (PML) (2.6 vs 0.5; p<0.02) and resulted in fewer alveolar macrophages (52,000 macrophages/ml BALF vs 68,000; p<0.05) compared to control mice. This improved NTCU + CS model is the first murine squamous cell lung cancer model to incorporate tobacco smoke and is more amenable to pre-clinical studies because of the increased number of PML, decreased number of mice required, and reduced time needed for PML development.